recurrences part 1
play

Recurrences, Part 1 Troy Vasiga Centre for Education in Mathematics - PowerPoint PPT Presentation

Recurrences, Part 1 Troy Vasiga Centre for Education in Mathematics and Computing Faculty of Mathematics, University of Waterloo cemc.uwaterloo.ca WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING Outline Short


  1. Mathematical Induction Mathematical induction is the mirror image of recursion. When we try to prove a result using induction, we need to do three things: 1. show the result holds for the base case(s): this is usually, but not always, easy 2. assume the result holds for all values ≤ k for some k which is at least as big as the base case(s) • this step is known as the inductive hypothesis • when we make this hypothesis, we are using strong induction • there is a variant known as weak induction where we assume the result holds only for one particular value of k 3. show the result holds for k + 1 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  2. Mathematical Induction Mathematical induction is the mirror image of recursion. When we try to prove a result using induction, we need to do three things: 1. show the result holds for the base case(s): this is usually, but not always, easy 2. assume the result holds for all values ≤ k for some k which is at least as big as the base case(s) • this step is known as the inductive hypothesis • when we make this hypothesis, we are using strong induction • there is a variant known as weak induction where we assume the result holds only for one particular value of k 3. show the result holds for k + 1 • this step is called the inductive step WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  3. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  4. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  5. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  6. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  7. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  8. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. We need to show that a k +1 = 5( k + 1). But, we know that a k +1 = 2 a k − a k − 1 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  9. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. We need to show that a k +1 = 5( k + 1). But, we know that a k +1 = 2 a k − a k − 1 = 2(5 k ) − 5( k − 1) WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  10. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. We need to show that a k +1 = 5( k + 1). But, we know that a k +1 = 2 a k − a k − 1 = 2(5 k ) − 5( k − 1) = 10 k − 5 k + 5 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  11. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. We need to show that a k +1 = 5( k + 1). But, we know that a k +1 = 2 a k − a k − 1 = 2(5 k ) − 5( k − 1) = 10 k − 5 k + 5 = 5 k + 5 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  12. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. We need to show that a k +1 = 5( k + 1). But, we know that a k +1 = 2 a k − a k − 1 = 2(5 k ) − 5( k − 1) = 10 k − 5 k + 5 = 5 k + 5 = 5( k + 1) WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  13. Our first inductive proof Prove: If a 0 = 0, a 1 = 5 and a n = 2 a n − 1 − a n − 2 , then a n = 5 n for all n ≥ 0. Proof: By (strong) mathematical induction. If n = 0, then 5 n = 0 = a 0 . If n = 1, then 5 n = 5 = a 1 . Thus, the result holds for the base cases. Assume that for all values of n such that n ≤ k , the result holds. That is, for any n ≤ k , we know that a n = 5 n . We now prove the result for n = k + 1. We need to show that a k +1 = 5( k + 1). But, we know that a k +1 = 2 a k − a k − 1 = 2(5 k ) − 5( k − 1) = 10 k − 5 k + 5 = 5 k + 5 = 5( k + 1) which proves the result. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  14. Exercise Suppose you have: a 0 = 1 a n = 2 a n − 1 + 1 (This is sometimes known as the Tower of Hanoi recurrence). Find a closed form, and prove that it is correct using mathematical induction. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  15. Solution Start with some values: a 0 = 1 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  16. Solution Start with some values: a 0 = 1 a 1 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  17. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  18. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  19. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  20. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 a 3 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  21. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 a 3 = 2(7) + 1 = 15 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  22. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 a 3 = 2(7) + 1 = 15 a 4 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  23. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 a 3 = 2(7) + 1 = 15 a 4 = 2(15) + 1 = 31 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  24. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 a 3 = 2(7) + 1 = 15 a 4 = 2(15) + 1 = 31 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  25. Solution Start with some values: a 0 = 1 a 1 = 2(1) + 1 = 3 a 2 = 2(3) + 1 = 7 a 3 = 2(7) + 1 = 15 a 4 = 2(15) + 1 = 31 We conjecture that a n = 2 n +1 − 1. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  26. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  27. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  28. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. We need to show that the result holds when n = k + 1. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  29. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. We need to show that the result holds when n = k + 1. a k +1 = 2 a k + 1 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  30. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. We need to show that the result holds when n = k + 1. a k +1 = 2 a k + 1 2(2 k +1 − 1) + 1 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  31. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. We need to show that the result holds when n = k + 1. a k +1 = 2 a k + 1 2(2 k +1 − 1) + 1 = 2 k +2 − 2 + 1 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  32. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. We need to show that the result holds when n = k + 1. a k +1 = 2 a k + 1 2(2 k +1 − 1) + 1 = 2 k +2 − 2 + 1 = 2 k +2 − 1 = WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  33. Proof of closed form We only have one base case: a 0 = 1 = 2 (0+1) − 1 Assume that for all n ≤ k ( k ≥ 0), we have a n = 2 n +1 − 1. We need to show that the result holds when n = k + 1. a k +1 = 2 a k + 1 2(2 k +1 − 1) + 1 = 2 k +2 − 2 + 1 = 2 k +2 − 1 = which proves the result. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  34. Formalizing a formula Guessing a closed form seems like a not very extendible idea, even for very “simple” things like: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  35. Formalizing a formula Guessing a closed form seems like a not very extendible idea, even for very “simple” things like: f 0 = 0 f 1 = 1 f n = f n − 1 + f n − 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  36. Formalizing a formula Guessing a closed form seems like a not very extendible idea, even for very “simple” things like: f 0 = 0 f 1 = 1 f n = f n − 1 + f n − 2 A recurrence is called linear if each term of a sequence defined by the recurrence is linear function (i.e., only multiplied by a constant or has a constant added) of earlier terms in the sequence. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  37. Formalizing a formula Guessing a closed form seems like a not very extendible idea, even for very “simple” things like: f 0 = 0 f 1 = 1 f n = f n − 1 + f n − 2 A recurrence is called linear if each term of a sequence defined by the recurrence is linear function (i.e., only multiplied by a constant or has a constant added) of earlier terms in the sequence. So, something like q n = ( q n − 1 ) 2 + 4 is not a linear recurrence, but all the other recurrences we have seen so far are linear. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  38. More formalism A linear homogeneous recurrence relation of degree k is a relation of the form a n = c 1 a n − 1 + c 2 a n − 2 + . . . + c k a n − k where each c i is a real number and c k � = 0. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  39. More formalism A linear homogeneous recurrence relation of degree k is a relation of the form a n = c 1 a n − 1 + c 2 a n − 2 + . . . + c k a n − k where each c i is a real number and c k � = 0. Such a recurrence must include k initial conditions: a 0 = V 0 a 1 = V 1 a k = V k . . . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  40. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  41. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . That would mean: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  42. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . That would mean: r n = c 1 r n − 1 + c 2 r n − 2 + · · · + c k r n − k WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  43. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . That would mean: r n = c 1 r n − 1 + c 2 r n − 2 + · · · + c k r n − k which we could rewrite as: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  44. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . That would mean: r n = c 1 r n − 1 + c 2 r n − 2 + · · · + c k r n − k which we could rewrite as: r n − c 1 r n − 1 − c 2 r n − 2 − · · · − c k r n − k = 0 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  45. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . That would mean: r n = c 1 r n − 1 + c 2 r n − 2 + · · · + c k r n − k which we could rewrite as: r n − c 1 r n − 1 − c 2 r n − 2 − · · · − c k r n − k = 0 and then we could divide both sides by r n − k to get: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  46. Characteristic equation Let’s suppose that the closed form to a recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k looks like a n = r n for some constant r . That would mean: r n = c 1 r n − 1 + c 2 r n − 2 + · · · + c k r n − k which we could rewrite as: r n − c 1 r n − 1 − c 2 r n − 2 − · · · − c k r n − k = 0 and then we could divide both sides by r n − k to get: r k − c 1 r k − 1 − c 2 r k − 2 − · · · − c k = 0 This is the characteristic equation of the recurrence. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  47. A helpful theorem Suppose we have the characteristic equation r k − c 1 r k − 1 − c 2 r k − 2 − · · · − c k = 0 for the recurrence a n = c 1 a n − 1 + c 2 a n − 2 + · · · + c k a n − k and there are solutions r 1 , r 2 , . . . r m to the characteristic equation. Then, a n = α 1 r n 1 + α 2 r n 2 + · · · + α m r n m satisfies the recurrence. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  48. Using this theorem Recall the Fibonacci recurrence: f 0 = 0 f 1 = 1 f n = f n − 1 + f n − 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  49. Using this theorem Recall the Fibonacci recurrence: f 0 = 0 f 1 = 1 f n = f n − 1 + f n − 2 The characteristic equation is: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  50. Using this theorem Recall the Fibonacci recurrence: f 0 = 0 f 1 = 1 f n = f n − 1 + f n − 2 The characteristic equation is: r 2 − r − 1 = 0 . Using the quadratic formula we get: ( − 1) 2 − 4(1)( − 1) � 1 ± r = 2 √ 1 ± 5 = 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  51. Solving the Fibonacci recurrence Thus, we know that √ √ � n � n � � 1 + 5 1 − 5 f n = α 1 + α 2 2 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  52. Solving the Fibonacci recurrence Thus, we know that √ √ � n � n � � 1 + 5 1 − 5 f n = α 1 + α 2 2 2 What to do next? WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  53. Solving the Fibonacci recurrence Thus, we know that √ √ � n � n � � 1 + 5 1 − 5 f n = α 1 + α 2 2 2 What to do next? Notice that we haven’t used our initial conditions: those will help us solve for α 1 and α 2 . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  54. Solving the Fibonacci recurrence Thus, we know that √ √ � n � n � � 1 + 5 1 − 5 f n = α 1 + α 2 2 2 What to do next? Notice that we haven’t used our initial conditions: those will help us solve for α 1 and α 2 . f 0 = α 1 + α 2 = 0 which means that α 2 = − α 1 . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  55. Using the second base case We know: √ √ � � � � 1 + 5 1 − 5 f 1 = α 1 + α 2 = 1 2 2 but we also know that α 2 = − α 1 from the previous page. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  56. Using the second base case We know: √ √ � � � � 1 + 5 1 − 5 f 1 = α 1 + α 2 = 1 2 2 but we also know that α 2 = − α 1 from the previous page. So, we have √ √ � � � � 1 + 5 1 − 5 − α 1 = 1 α 1 2 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  57. Using the second base case We know: √ √ � � � � 1 + 5 1 − 5 f 1 = α 1 + α 2 = 1 2 2 but we also know that α 2 = − α 1 from the previous page. So, we have √ √ � � � � 1 + 5 1 − 5 − α 1 = 1 α 1 2 2 which implies WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  58. Using the second base case We know: √ √ � � � � 1 + 5 1 − 5 f 1 = α 1 + α 2 = 1 2 2 but we also know that α 2 = − α 1 from the previous page. So, we have √ √ � � � � 1 + 5 1 − 5 − α 1 = 1 α 1 2 2 which implies √ √ � � 1 + 5 − 1 − 5 = 1 α 1 2 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  59. Using the second base case We know: √ √ � � � � 1 + 5 1 − 5 f 1 = α 1 + α 2 = 1 2 2 but we also know that α 2 = − α 1 from the previous page. So, we have √ √ � � � � 1 + 5 1 − 5 − α 1 = 1 α 1 2 2 which implies √ √ � � 1 + 5 − 1 − 5 = 1 α 1 2 2 √ � � 2 5 1 and so α = 1, which implies α 1 = 5 . √ 2 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  60. Solution Thus, the Fibonacci sequence has closed form: √ √ � n � n � � 1 1 + 5 − 1 1 − 5 f n = √ √ 2 2 5 5 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  61. Golden ratio Notice that if we have a and b satisfying: a + b = a b b WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  62. Golden ratio Notice that if we have a and b satisfying: a + b = a b b then a b = ϕ , where √ ϕ = 1 + 5 2 . WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  63. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  64. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  65. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  66. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 which you can solve by factoring to get WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  67. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 which you can solve by factoring to get ( r − 1) 2 = 0. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  68. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 which you can solve by factoring to get ( r − 1) 2 = 0. Thus, r = 1 is a solution. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  69. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 which you can solve by factoring to get ( r − 1) 2 = 0. Thus, r = 1 is a solution. Problem: a n = α 1 (1) n + α 2 (1) n for FIXED α 1 and α 2 has no solution! WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  70. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 which you can solve by factoring to get ( r − 1) 2 = 0. Thus, r = 1 is a solution. Problem: a n = α 1 (1) n + α 2 (1) n for FIXED α 1 and α 2 has no solution! Fortunately, we can augment our theorem: WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

  71. Theorem isn’t exact enough yet Recall: a n = 2 a n − 1 + a n − 2 with a 0 = 0 and a 1 = 5. The characteristic polynomial is: r 2 − 2 r − 1 = 0 which you can solve by factoring to get ( r − 1) 2 = 0. Thus, r = 1 is a solution. Problem: a n = α 1 (1) n + α 2 (1) n for FIXED α 1 and α 2 has no solution! Fortunately, we can augment our theorem: If there is a root r i with multiplicity m + 1 (i.e., ( r − r i ) m +1 is a factor), then r n i , nr n i , . . . n m r n i are all solutions of the recurrence. WWW.CEMC.UWATERLOO.CA | The CENTRE for EDUCATION in MATHEMATICS and COMPUTING

Download Presentation
Download Policy: The content available on the website is offered to you 'AS IS' for your personal information and use only. It cannot be commercialized, licensed, or distributed on other websites without prior consent from the author. To download a presentation, simply click this link. If you encounter any difficulties during the download process, it's possible that the publisher has removed the file from their server.

Recommend


More recommend